Triazapolycarboxylate-based Ga(III) and Mn(II) chelates for medical imaging (PET, gamma-scintigraphy and MRI) - Sá, Arsénio Vasconcelos (2014)
Tese de doutoramento em Ciências (área de especialização em Química)